Additive manufacturing with stimuli-responsive materials. Issue 42 (22nd October 2018) - Boydston, A. J.; Cao, B.; Nelson, A.; Ono, R. J.; Saha, A.; Schwartz, J. J.; Thrasher, C. J.
Abstract : Additive manufacturing, commonly referred to as 3D printing (3DP), has ushered in a new era of advanced manufacturing that is seemingly limited only by imagination. Abstract : Additive manufacturing, commonly referred to as 3D printing (3DP), has ushered in a new era of advanced manufacturing that is seemingly limited only by imagination. In actuality, the fullest potentials of 3DP can only be realized through innovative breakthroughs in printing technologies and build materials. Whereas equipment for 3DP has experienced considerable development, molecular-scale programming of function, adaptivity, and responsiveness in 3DP is burgeoning. This review aims to summarize the state-of-the-art in stimuli-responsive materials that are being explored in 3DP. First, we discuss stimuli-responsiveness as it is used to enable 3DP. This highlights the diverse ways in which molecular structure and reactivity dictate energy transduction that in turn enables 3D processability. Second, we summarize efforts that have demonstrated the use of 3DP to create materials, devices, and systems that are in their final stage stimuli-responsive. This section encourages the artistic license of advanced manufacturing to be applied toward leveraging, or enhancing, energy transduction to impart device function across multiple length scales.